2012
DOI: 10.2355/isijinternational.52.984
|View full text |Cite
|
Sign up to set email alerts
|

Influence of B2O3 on Viscosity of High Ti-bearing Blast Furnace Slag

Abstract: The influence of B2O3 on the viscosity of high Ti-bearing BF slag is studied under Ar atmosphere from 1 773 K (1 500°C) to about 1 593 K (1 320°C). The results show that the addition of B2O3 can decrease the viscosity of high Ti-bearing BF Slag containing UPC, consequently improve its fluidity. With the existence of 1.5% UPC, when the content of B2O3 increased from 0 to 4.1%, the volume fraction of perovskite decreased from 7.7% to 1.6% at 1 610 K. Meanwhile, the liquidus temperatures decreased from 1 619 K to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 21 publications
1
46
0
Order By: Relevance
“…Studies on viscous flow behaviors of the borosilicate melts [17][18][19][20] generally show a decreasing viscosity with increasing B 2 O 3 content in the melts. In addi-tion, in a previous study on crystallization behaviors, 21) we found that a B 2 O 3 addition of 5% brought about a drastic change of primary crystalline phase in a CaO-SiO 2 -MgOAl 2 O 3 -TiO 2 -B 2 O 3 melt, viz., from CaTiO 3 to TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies on viscous flow behaviors of the borosilicate melts [17][18][19][20] generally show a decreasing viscosity with increasing B 2 O 3 content in the melts. In addi-tion, in a previous study on crystallization behaviors, 21) we found that a B 2 O 3 addition of 5% brought about a drastic change of primary crystalline phase in a CaO-SiO 2 -MgOAl 2 O 3 -TiO 2 -B 2 O 3 melt, viz., from CaTiO 3 to TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…However, they also recently found that a decrease in viscosity occurs at higher B 2 O 3 concentrations in CaO-SiO 2 -B 2 O 3 -TiO 2 -based systems, and presumed that this results from the weaker bond energy of B-O compared to Si-O or alkaline earth metal-oxygen bonds. 11) In the blast furnace slag system, according to Ren et al,20) even though the addition of boron oxide increases the amount of 4-coordinated boron oxide ([BO 4 ] 5-), the viscosity is nonetheless reduced by a lowering of the eutectic temperature. Similarly the complicated effects of B 2 O 3 on its physical properties were also pointed out by Fox et al 18) They reported that because of the formation of three-fold and/or four-fold co-ordination of borosilicates, the effect of B 2 O 3 was to create both a decrease and increase in viscosity for various mold flux systems.…”
Section: Introductionmentioning
confidence: 99%
“…9(d)-9(f), where initial crystallization temperature is getting higher with the increase of B2O3 changing from 834°C to 865°C and 901°C respectively, when B2O3 contents becomes from 6.03% to 8.00% and 10.03 mass%. Boron, as one of the network former, 27,28) could form the trigonal planar [BO3] 3-…”
Section: Experiments Proceduresmentioning
confidence: 99%